Research-training workshops for the design competence development of Lower Secondary School Teachers - Capperucci, Davide (Formazione & insegnamento, 2017)
This paper analyses the role design competence plays in the professional development profile of lower secondary school-teachers, together with how this competence can be developed within the new initial training programme for teachers envisaged by the so-called “FIT”-track. The competence linked to teaching and curriculum design is a “complex know-how” which draws on many other competences such as pedagogical, relational, assessment and evaluation, organizational, and digital ones among others; all of these are necessary to develop effective teaching interventions which can fulfill the educational needs of students. It is because this is a composite and articulated competence that it is extremely important that this competence be developed from the very first stages of teacher-training through the use of research-training workshops which enable the interaction of the theoretical as well as the operational-methodological dimensions, the heuristic-phenomenological and hermeneutic-reflective aspects of teaching. To this end, this paper proposes a possible research-training workshop model which aims to develop the design competences of teachers which can be used so as to support the growing awareness of what is involved in teaching.